Antonymy in the Language Style of the Qur’an - Idris, Mardjoko (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2016)
Al-Quran is the Holy Book that has received recognition from Allah SWT as a perfect Book. As a perfect Holy Book, al-Quran ismu’jiz (that debilitates). One aspect of i’jâz of al-Quran is in its language aspects, one of the aspect is the Antonymy orat-tadhâdu. This research would focus on the study of Antonymy in the language style of al-Quran, as well as some examples of its antonymic word/lafadz. Theory used in the analysis wasal-Khammas which distinguishes antonym into four types namely Absolute Antonym, Complex Antonym, Converse Antonym, Sideline Antonym/Straight Line Antonym. This research focuses on the issues of What types of antonymy found in the language style of al-Quran? And What Lafadz of antonymy found in the language style of al-Quran?As the results of the study, types of antonymy found in the language style of al-Quran were (a) one word/lafadz which has two contradictory meanings in one verse, (b) one word/lafadz which has two contradictory meanings in two verses, and (c) two words/lafadz which are contradictory in meanings in one verse.Keywords: Antonymy, Thibâq, Muqâbalah